2011
DOI: 10.1177/1744987111410659
|View full text |Cite
|
Sign up to set email alerts
|

Do perimenopausal and menopausal symptoms affect the marital relationship?

Abstract: This study investigated whether women's perimenopausal/menopausal symptoms had negative effects on marital or long-term relationships, an aspect underrepresented in the literature. A questionnaire distributed to 110 convenience-sampled women, ages 45-60 years and prescreened for inclusion by private practitioners or the author's colleagues, yielded a 60% return. Symptoms correlated positively with participants' feelings about the relationship and sexual intimacy with their partner (.353-.783, p ¼ 0.01, and 272… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, the difference in the previous results could be related to the degree of marital satisfaction of menopausal women. This is supported by Caico (2013) who reported that women who experienced greater marital satisfaction have been shown to have less severe menopausal symptoms and negative moods (26) . While Roesch et al, (2021) found that no significant difference was found between the mean ENRICH Marital Satisfaction score for women who report that they are in menopause and not in menopause (27) .…”
Section: Masjoudi Et Al (2017) Revealed That549%mentioning
confidence: 71%
“…In addition, the difference in the previous results could be related to the degree of marital satisfaction of menopausal women. This is supported by Caico (2013) who reported that women who experienced greater marital satisfaction have been shown to have less severe menopausal symptoms and negative moods (26) . While Roesch et al, (2021) found that no significant difference was found between the mean ENRICH Marital Satisfaction score for women who report that they are in menopause and not in menopause (27) .…”
Section: Masjoudi Et Al (2017) Revealed That549%mentioning
confidence: 71%
“…() found that menopausal women in China believe that as age increases, sexual relationships decrease in importance or significance. Caico's () study of menopausal women in the US also found that some menopausal women viewed spouses as companions or friends. It may be that, with increasing age or with menopausal status, women's concern turns more to emotional intimacy rather than sexual intimacy (Tiegs et al .…”
Section: Discussionmentioning
confidence: 97%
“…Menopause or the wider context of women's lives and relationships? It is perhaps unsurprising that researchers have sometimes concluded that hormones and peri/menopausal changes may be a factor in relationship breakdown and marriages ending (Caico, 2011;Wu & Schimmele, 2007). Yet, this is difficult to definitively ascertain.…”
mentioning
confidence: 99%
“…The reasons for women considering leaving a partner/relationship during midlife could be attributed to other aspects of having been partnered for many years. It is also particularly difficult to tease apart peri/menopause from other changes within women's wider contexts (e.g., Caico, 2011). Research during the 1990s and early 2000s evidenced how challenges associated with caring for ageing parents, their own partner's health and sexual functioning, and low levels of social support impacted women's relationships (reported in Hinchliff et al, 2010; see also Dillaway, 2007Dillaway, , 2008Dillaway, , 2020.…”
mentioning
confidence: 99%
See 1 more Smart Citation